Burden of caregiving, social support and quality of life of informal caregivers of patients with cerebral palsy - Chidimma J. Ahanotu; Peter O. Ibikunle; Adebisi I. Hammed (Turkish Journal of Kinesiology, 2018)
The study investigated the burden of caregiving, social support and quality of life of informal caregivers of patients with CP. The study adopted a cross-sectional survey research design. A total of 78 informal caregivers participated in this study. The quality of life was assessed using the World Health Organization Quality of Life Bref (WHOQOL-Bref). Also, social support was assessed using Multidimensional Scale of Perceived Social Support (MSPSS). However, the level of burden of caring for CP patients on caregivers was estimated with the use of Caregivers Strain Index (CSI). The Spearman Rank Order Correlation test was used to test the correlation among the caregivers' quality of life, social support, and burden and some patient and caregiver related variables. The statistical significance was accepted for a p value of <0.05. The outcome of this study showed that the degree of strain on the caregivers was significant, same as the impact on their quality of life. However, the caregivers' level of strain has no significance on their level of perceived social support. Also, majority of the caregivers in this study experienced a considerable amount of burden and the level of perceived social support of caregivers was moderate. The caregivers also had a high quality of life in all domains. It was therefore concluded that caring for a child with CP had significant impact on the level of burden, social support and quality of life of informal caregivers. Also, the informal caregiver had a significant level of burden, a moderate of social support mainly from family and significant others and a high level of quality of life. It was thus recommended that study should be carried out to compare the level of burden, perceived social support and quality of life between informal caregivers of patients with CP and caregivers of healthy children.